Edukasi Kesehatan Tentang Pemanfaatan Puding Labu Kuning untuk Penurunan Tekanan Darah di Desa Cot Paya - Nurul Sakdah; Ellyza Fazlylawati; Putriyani Putriyani; Meilisa Meilisa; Defri Mahendra; Mina Indrianti; Tamara Agustina; Alfiaturrahmi Alfiaturrahmi; Ismayani Ismayani; Siti Humairah; Savinatun Najja; Ulan Maulidia; Muhammad Bayta’wi; Hayatul Firda; Humaira Humaira; Beny Bilo; Muhammad Baihaqi; Misra Aulisa (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Background: Hypertension is a chronic disease where blood pressure is above the normal limit, namely 140/90 mmHg, one of the causes of hypertension is a lack of potassium. Pumpkin with high levels of potassium and fiber can help to lower blood pressure. Purpose of service: Providing health education about the use of pumpkin pudding to lower blood pressure. Method: The method used in this service activity is lecture and question and answer. Results: The results of providing education and knowledge about hypertension to families and the elderly were responded well by the Cot Paya community, then several parents asked questions based on material about hypertension. Conclusion: Understanding of families and elderly in Cot Paya village regarding how to use pumpkin pudding to reduce blood pressure.